On the taxonomy of the desert lizard Liolaemus stolzmanni (Steindachner, 1891): A third point of view (Squamata: Liolaemidae) - Troncoso-Palacios, Jaime; Escobar-Gimpel, Víctor (Zootaxa, 2020)
Recently, two publications, Langstroth (2011) and Valladares-Faúndez et al. (2018), have provided relevant information on the taxonomy of the poorly know South American lizard, Liolaemus stolzmanni (Steindachner 1891).. However, these publications contradict each other, in regards to L. reichei (Werner 1907) as junior synonym of L. stolzmanni and did not solve the problem of the type locality of L. stolzmanni. In fact, currently the type locality of L. stolzmanni is thought to be imprecise because the description (Steindachner 1891), written in German, stated it as “Hoch Peru” (High Peru), which has been erroneously understood as “northern Peru” or “high altitudes from Peru”, a zone in which L. stolzmanni has been never found. Here, we used the book of memories of Jan Stanisław Sztolcman, the Polish collector, a historical data never taken in account before, to restrict the type locality and provide comments on its taxonomy.